Correlation of Patient Visits to Dental Treatment Procedures: Case Study of Hospital X in Bontang - Suhargiati, Atik (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Hospitals play a vital role in healthcare delivery, with medical records essential for informed decision-making. Increased public health awareness has resulted in a rise in patient visits, particularly in dental departments. Objective : This research examines the relationship factors between patient visits and dental treatments at Hospital X in Bontang from July to September 2023, focusing on the influences of age and gender. Research Methods/ Implementation Methods : A quantitative observational study included all 375 dental patients during the specified period. Data on demographics and dental treatment procedures were collected and analyzed using Pearson correlation and T-tests. Results : : A significant correlation (r = 0.7317) was found between patient visits and treatment complexity. Male patients showed a correlation of 0.398, while female patients had 0.280. T-test results confirmed statistical significance Conclusion/Lesson Learned : Demographic factors significantly impact dental care complexity, highlighting the need for targeted resource allocation to enhance patient outcomes.